Proceedings of the 9th Economics &Amp; Finance Conference, London 2018
DOI: 10.20472/efc.2018.009.009
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities and Migration in Member States Eu

Abstract: Certainly, the spatial distribution of economic activities is far from uniform in many countries European Union and significant differences at national and at regional level are still persistent. The aim of this study is to investigate and compare regional disparities in member states of European Union and estimate the effect of regional migration flows on convergence of regions. This study focuses on income and employment, these two factors are considered as major determinants of migration and on the contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…According to Popademetriou (1985), migration robbed poor countries of their skilled manpower and often left countries with unproductive members of the population once the young and middle-aged have migrated to rich developed countries. Though the migration of the unskilled created no major concerns, the migration of skilled citizens has been lamented as depriving poor countries of their scarce human capital, leading to grave concerns about the brain drain (De Haas, 2010;Kurekova, 2011;Wood, 1982).…”
Section: Neo-marxism: Adverse Correlation Between Migration and Devel...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Popademetriou (1985), migration robbed poor countries of their skilled manpower and often left countries with unproductive members of the population once the young and middle-aged have migrated to rich developed countries. Though the migration of the unskilled created no major concerns, the migration of skilled citizens has been lamented as depriving poor countries of their scarce human capital, leading to grave concerns about the brain drain (De Haas, 2010;Kurekova, 2011;Wood, 1982).…”
Section: Neo-marxism: Adverse Correlation Between Migration and Devel...mentioning
confidence: 99%
“…The shift in social theory resulted in the emergence of new theories of migration such as the NELM which expanded the neo-classical economic theory of migration by creating space for sociological aspects such as social capital and the analysis of migrants in the context of social groups (Cassarino, 2004;De Haas, 2010;Kurekova, 2011). NELM was a welcome addition to the migration-development debate in the 1980s and 1990s as it affirmed the plurality of migration and the outcomes thereof.…”
Section: Pluralist Migration-development Positive Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…They considered the migration from new EU members (EU8) to the EU15 in the period 2004-2007 and they found significant positive effects of migration on GDP, while the impact on labour markets was small in the short term (decline of wages in EU15, increase of wages in EU8, unemployment rates increase in EU15 and decrease in EU8) and neutral in the long term. Kureková (2018) researched the impact of migration on economic regional convergence within the EU, focusing on employment and income. By applying the panel data analysis, she found that migration can contribute to reducing disparities in employment rates and income between regions.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Theories underpinning the study are the neoclassical economic theory and the new economics of labour migration (Kurekova 2011 ). According to Borjas (1990) as cited in Castles ( 2000 :2), the neoclassical economic theory holds that ‘the main cause of migration is the individual’s efforts to maximize their income by moving from low to high wage economies’.…”
Section: Introductionmentioning
confidence: 99%